2012
DOI: 10.1515/cclm-2011-0787
|View full text |Cite
|
Sign up to set email alerts
|

Population-based pediatric reference intervals for general clinical chemistry analytes on the Abbott Architect ci8200 instrument

Abstract: The data generated is primarily applicable to a Caucasian population when using the Abbott Architect platform, but could be used by any laboratory if validated for the local patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 23 publications
4
29
3
1
Order By: Relevance
“…However, calculation of reference intervals revealed that several age and sex partitions were required to reflect minor fluctuations in electrolyte concentrations, i.e., chloride and sodium each required 4 age partitions, whereas potassium required 2. Although our data agree with the range of reference values that are typical for healthy individuals, the robust dataset demonstrates an even more complex pattern than previously observed (11)(12)(13). Another large study of Ͼ7000 Chinese adults aged 20 -79 years showed a similar electrolyte profile, in which at least 6 age partitions were required for electrolytes (14 ), further supporting the requirement of a large sample population to fully capture such minor fluctua- To maintain participant confidentiality (on the basis of Statistics Canada policy), each data point represents the mean of ≥11 closely associated data points.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, calculation of reference intervals revealed that several age and sex partitions were required to reflect minor fluctuations in electrolyte concentrations, i.e., chloride and sodium each required 4 age partitions, whereas potassium required 2. Although our data agree with the range of reference values that are typical for healthy individuals, the robust dataset demonstrates an even more complex pattern than previously observed (11)(12)(13). Another large study of Ͼ7000 Chinese adults aged 20 -79 years showed a similar electrolyte profile, in which at least 6 age partitions were required for electrolytes (14 ), further supporting the requirement of a large sample population to fully capture such minor fluctua- To maintain participant confidentiality (on the basis of Statistics Canada policy), each data point represents the mean of ≥11 closely associated data points.…”
Section: Discussionsupporting
confidence: 85%
“…Declining phosphate concentrations likely reflect both the cessation of bone growth after puberty and various stages of bone mineralization, as exemplified by the low values observed from 48 to 79 years of age. High total calcium and phosphate in childhood have previously been observed in the CALIPER study (1 ), and the downward trends with age are corroborated by other studies (13,15 ). Interestingly, the lower calcium and phosphate values observed for females have also been reported by some groups (11 ) but not others (14 ).…”
Section: Discussionsupporting
confidence: 76%
“…Approximately 50 analytes were measured, and the results for the other analytes have been presented elsewhere [18,19,20,21]. The Regional Ethical Review Board of Uppsala (No.…”
Section: Methodsmentioning
confidence: 99%
“…The present study is part of a larger project [18] designed to define reference intervals for general clinical chemistry in healthy children 6 months to 18 years of age. The aim is to define the prevalence of elevated ALP in a population of apparently healthy children, and to calculate age- and gender-specific pediatric reference intervals for serum ALP.…”
Section: Introductionmentioning
confidence: 99%
“…Ovo je moguće pod uslovom da se i proizvođači opreme pridržavaju propisanih standarda, primenjuju savremene statističke metode i izvode multicentrične studije [6]. Danas se zajednički RV formiraju u određenom regionu jedne zemlje ili u nekoliko zemalja, dok se ostale laboratorije oslanjaju na ovako dobijene vrednosti [7,8].…”
Section: Discussionunclassified